The global existence and asymptotic stability of solutions for a reaction–diffusion system. (June 2020) - Bendoukha, Samir; Abdelmalek, Salem; Kirane, Mokhtar
Abstract: This paper studies the solutions of a reaction–diffusion system with nonlinearities that generalize the Lengyel–Epstein and FitzHugh–Nagumo nonlinearities. Sufficient conditions are derived for the global asymptotic stability of the solutions. Furthermore, we present some numerical examples.